Optimal boundary control in a micromixer - Manuel Wegmann; Julius Jeßberger; Gudrun Thäter; Mathias J. Krause (Examples and Counterexamples)
This work studies mathematical foundations for optimal boundary control of mixers which mix two fluid phases. Existence of optima is proved and the influence of common objective functionals is discussed.